DHA Ameliorates Cognitive Ability, Reduces Amyloid Deposition, and Nerve Fiber Production in Alzheimer’s Disease - Xiao, Min; Xiang, Wei; Chen, Yashu; Peng, Nan; Du, Xiubo; Lu, Shuhuan; Zuo, Yao; Li, Boling; Hu, Yonggang; Li, Xiangyu (Frontiers in Nutrition, 2022)
Background: The etiology of Alzheimer's disease (AD) is very complex. Docosahexaenoic acid (DHA) is important in cognitive ability and nervous system development. A limited number of studies have evaluated the efficacy of DHA in the treatment of AD. Introduction: We detect neurofibrillary tangles (NFT) in the hippocampus and cortex of transgenic mice brain through silver glycine staining. We determined the activity of neurons by staining Nissl bodies, used liquid NMR to detect metabolites in the brain, and functional magnetic resonance imaging results to observe the connection signal value between brain regions. Materials and Methods: We fed 3-month-old APP/PS1 double transgenic mice with DHA mixed feeds for 4 months to assess the effects of DHA on cognitive ability in AD mice through the Morris water maze and open field tests. To evaluate its effects with AD pathology, continuous feeding was done until the mice reached 9 months of age. Results: Compared to AD mice, escape latency significantly decreased on the fifth day while swimming speed, target quadrant stay time, and the crossing number of platforms increased by varying degrees after DHA treatment. Brain tissue section staining revealed that DHA significantly reduced Aβ and nerve fibers in the brain of AD mice. Conclusion: DHA significantly reduced the deposition of Aβ in the brain and inhibited the production of nerve fibers, thereby increasing cognitive abilities in AD mice. In addition, DHA suppressed blood lipid levels, and restored uric acid and urea levels, implying that DHA is a potential therapeutic option for early AD.